Traditional salads in Malaysia: potential for pitfalls in cytology diagnostic. / Intan Nur Shahfiqah Baharum - Baharum, Intan Nur Shahfiqah (2015)
Introduction: Pitfalls in cytology refer to misinterpretation of finding which can cause false positive or negative. Misdiagnosed cases in gyne and non-gyne samples can affect treatment and morbidity. Furthermore, food contaminant such as fruits and vegetables can interfere during interpretation. Traditional Salads consumed by Malaysian, called 'ulam' is a possible contamination that can mimic during cytology diagnosis. The objective of this study is to describe the morphology of traditional salads cells in Malaysia and to identify the mimicking characters of these cells with normal, abnormal and microorganism from cytology samples. Method: Random traditional salads from Malaysia were selected and homogenize using mortar and pestle. This is to resemble chewing affect by breaking down the cell into single cells. Each sample then smeared onto two glass slide with back to back method. One smeared slide was fixed using 95% of ethanol to retain cell structure and stain using Papanicolaus stain. The other smeared slide was left on air dried and stain using May Grunwald's stain. The cells then observed and capture using Laica DM750 Microscope with an ICC 50HD camera. Result: Petai cells mimic clue cells in bacterial vaginosis and also Trichomonas vaginalis ghostly appearance. Bestowed, Asiatic pennywort and water dropwort have mimicking character of glandular cells of endocervical. Ulam raja mimics thecharacter of endometrial. Meanwhile, sweet leaf has the character of squamous cells. Conclusion: Most of traditional salads cells described in these study mimic normalcells while others mimic parasitic infection and bacterial vaginosis. Therefore, morphology of traditional salad cells in Malaysia can mimic human cells and cause pitfalls during cytology diagnostic. These finding can be used as a reference in cytology diagnostic to minimize the rate of pitfall, lead to proper treatment, and can safe life.